The last of the sky pirates / 5. - Stewart, Paul, 1955- (Stewart, Paul, 1955- Edge chronicles, 2005)
Rook Barkwater, one of the apprentices chosen to make a dangerous journey to study in the Deepwoods, joins the sky pirate Captain Twig in opposing the Guardians of the Night and learns more about his own past.